An Initial-boundary-value Problem for the Modified Korteweg-de Vries Equation in a Quarter Plane (Journal of Partial Differential Equations, 2020)
In this paper, we obtain some linear estimates, trilinear estimates. Through these estimates, we prove the local wellposeness of modified Korteweg-de Vries equation in a quarter plane.
Keywords: the modified Korteweg-de Vries equation; initial-boundary-value problem; well-posedness